Potential Applications of Endo-β-N-Acetylglucosaminidases From Bifidobacterium longum Subspecies infantis in Designing Value-Added, Next-Generation Infant Formulas - Duman, Hatice; Kaplan, Merve; Arslan, Ayşenur; Sahutoglu, Arif Sercan; Kayili, Haci Mehmet; Frese, Steven A.; Karav, Sercan (Frontiers in Nutrition, 2021)
Human milk is the optimal source of infant nutrition. Amongst many other health benefits, human milk can stimulate the development of a Bifidobacterium-rich microbiome through human milk oligosaccharides (HMOs). In recent years, the development of novel formulas has placed particular focus on incorporating some of the beneficial functional properties of human milk. These include, adding specific glycans aimed to selectively stimulate the growth of Bifidobacterium. However, the bifidogenicity of human milk remains unparalleled. Dietary N-glycans are carbohydrate structures conjugated to a wide variety of glycoproteins. These glycans have a remarkable structural similarity to HMOs, and when released show a strong bifidogenic effect. This review discusses the biocatalytic potential of the Endo-β-N-acetylglucosaminidase enzyme (EndoBI-1) from Bifidobacterium longum subspecies infantis, in releasing N-glycans inherently present in infant formula as means to increase the bifidogenicity of infant formula. Finally, the potential implications for protein deglycosylation with EndoBI-1 in the development of value added, next-generation formulas are discussed from a technical perspective.